Late Roman pottery with stamped decoration from Serdica (Sofia, Bulgaria) - Borisova-Katsarova, Iliana (Rei Cretariae Romanae Fautorum Acta, 2024)
The article discusses preliminary results from the study of late antique pottery known in the literature as "grey Macedonian terra sigillata”, discovered during archaeological excavations in ancient Serdica, Bulgaria. The investigations show that the leading feature of these vessels – stamped decoration, is found both on vessels of grey and black surface, and on vessels of red colour. At the same time, technological features of vessels without decoration, but made of similar clay and similar surface treatment suggest that they can be grouped into a type of undecorated and decorated tableware, distributed in a large area in the Late Antique prefecture of Illyricum, but mainly in its Eastern part. Preliminary results of interdisciplinary research reveal new details about the production technology. The outlined area of distribution suggests that this ceramic complex is associated with a population engaged in mining and metallurgy, settled in these lands at the beginning of Late Antiquity.